ANALYSIS OF DIVORCE CASES IN THE BATUSANGKAR RELIGIOUS COURTS IN THE PERSPECTIVE OF LAW NUMBER 23 OF 2004 CONCERNING THE ELIMINATION OF DOMESTIC VIOLENCE - Wulandari, Sri; Eficandra, Eficandra; Effendi, Amri; Octavia, Nurul Aini (Institut Agama Islam Negeri Batusangkar, 2024)
This research examines forms of domestic violence and the considerations of judges at the Batusangkar Religious Court in deciding divorce cases and judges' considerations in divorce cases from the perspective of Law Number 23 of 2004 concerning the Elimination of Domestic Violence. The type of research used in writing this thesis is a qualitative approach. The results of the first research, forms of domestic violence in divorce cases. Second, the consideration of the judge at the Batusangkar Religious Court in deciding a divorce case, one party leaving the other party for 2 (two) consecutive years, a prison sentence of 5 (five) years, the husband violating the divorce agreement. The three judge's considerations regarding divorce cases are seen from the perspective of Law Number 23 of 2004.